Pecularities of hematological disorders in the Chernobyl accident consequence combatants 10–12 years after the disaster - Stepanenko, I. V. (Ukrainian Neurosurgical Journal)
Hematological monitoring showed that the Chernobyl accident consequence combatants who had been exposed to relatively small-dose radiation maintain for a long time the wave-type hemopoietic disorders which are evidence for the processes of hemopoiesis effort and the presence of intoxication and allergy syndromes as well as the sign of immunodeficiency.